Pendekatan Pembangunan Wilayah Berbasis Komunitas untuk Pengembangan Pariwisata Berkelanjutan di Desa Luthu Lamweu - Elysa Wulandari; Myna Agustina Yusuf; Winda Hanifah; Siti Zahrina Fakhrana (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines community empowerment strategies to develop Luthu Lamweu Village as a sustainable tourism destination based on community-based tourism (CBT). Strategically located in Sukamakmur District, Aceh Besar Regency, the village boasts significant tourism potential, including natural landscapes, cultural traditions, and local products such as handicrafts and traditional cuisine. However, this potential remains underutilized due to inadequate infrastructure, weak institutional frameworks, limited community capacity in tourism management, and suboptimal promotional efforts. The research utilized a descriptive method with data collected through interviews, questionnaires, observations, and Focus Group Discussions (FGD).